Creating the Habitus of Tolerance in Indonesian Schools: Normative, Praxis, and Symbolic Dimensions - Pattinasarany, Indera Ratna Irawati; Kusumadewi, Lucia Ratih; Setiadi, Aditya Pradana (UI Scholars Hub, 2022)
In a multicultural society, tolerance is an important prerequisite for maintaining social order in communal life. Schools are one of the most important loci for habituating a character and culture of tolerance. However, most studies that have been carried out tend to focus more on the problem of intolerance in schools, and have not explored how the habitus of tolerance can be created and practiced instead. This research is a study on how nine schools in seven different cities across Indonesia have developed their own habitus of tolerance. We employed a qualitative research method with in-depth interviews, observa¬tion, and document review data collection techniques. The study shows that the habitus of tolerance in schools is realized through three dimensions. First, the normative dimension, namely through values, norms, and regulations. Second, the practical dimension, namely through the learning process at school in the form of activities and created habits. Third, the symbolic dimension, namely through the use of material symbols.